Research on Surface Defects of 304 Austenitic Stainless Steel - Wang Weilong; Shen Hao; Gu Qianning; Zhang Rui; Wang Jiahao; Shi Xi (E3S Web of Conferences, 2024)
A company prepared 304 stainless steel screws through drawing, cold heading, and punching treatment processes. Cracks appeared at the cross hole of the nut, and a large number of samples had cracks. After inclusion analysis, metallographic analysis, and flow pattern analysis, it was found that the cracking of the cap was mainly caused by excessive pressure during the punching process. Subsequently, the punching pressure was reduced by 20 MPa, and the problem of cap cracking was solved.